Analisis Reduplikasi pada Koran Joglo Semar Edisi Bulan September 2016 dengan Kajian Morfologidan Implementasinya pada Pembelajaran Bahasa di SMP - Safitri, Ratna Ristika (2017)
This study aims to (1) describe the process of reduplication contained in newspapers JogloSemar edition in September 2016, (2) describe the process and meaning reduplication found in newspapers JogloSemar edition in September 2016, and (3) explain the implementation of reduplicated form contained at JogloSemar newspaper edition in September 2016 on language learning in junior high. This study used descriptive qualitative method. Sources of data obtained from the discourse in newspapers JolgoSemar, 2016. The September issue of data analysis technique used is the technique BUL with agih method. The results of this study were (1) Process reduplications contained in newspapers JogloSemar edition in September 2016 there were four, namely (a) the repetition of the whole, (b) repetition portion, (c) the repetition combined with the process of affixing affixes, and (d ) repetition with change of phonemes. The majority of reduplication found in JogloSemar newspaper edition in September 2016 is a repetition of the whole because it caused within the rubric of the newspaper delivery technique. (2) The meaning of repetition reduplications contained in JogloSemar newspaper edition in September 2016 is a lot, a little, unconditional, no-nonsense, quality and repetitive. However, the more common meaning many and repeated as a picture of an event within the rubric of JogloSemar newspaper edition in September 2016. (3) The relevance of the research results reduplications contained in JogloSemar newspaper edition in September 2016 with the Competence Standard and Basic Competence 4.1 and 4.2. . Keyword : reduplication, morphology studies, language learning in junior high school.